Determinan Keberhasilan Pengobatan Pasien Tuberkulosis di Kota Pangkalpinang Tahun 2025 - Fitriadi Fitriadi; Rico Januar Sitorus; Taufik Kurrohman; Dedek Sutinbuk; Heru Listiono (CV. Global Cendekia Inti, 2026)
Tuberculosis (TB) remains a significant public health challenge in Indonesia. Treatment success is a crucial benchmark in TB control efforts, influenced by various patient- and health system-related factors. This study aimed to examine the determinants of treatment success among tuberculosis patients in Pangkalpinang City during 2025. This quantitative analytical study employed a cross-sectional design using secondary data from the Tuberculosis Information System (SITB) of the Pangkalpinang City Health Office. The sample consisted of 874 TB patients who met the inclusion criteria, selected via total sampling. Data analysis involved univariate, bivariate (Chi-Square test), and multivariate (logistic regression) methods. The TB treatment success rate was recorded at 90.3%. Bivariate analysis revealed that HIV status was significantly correlated with treatment success (p<0.001), whereas age (p=0.082), gender (p=0.738), and type of health facility (p=0.090) did not show significant associations. Multivariate analysis results indicated that age (POR=1.697; 95%CI=1.046-2.754; p=0.032), HIV status (POR=2.172; 95%CI=1.642-2.872; p<0.001), and type of health facility (POR=2.468; 95%CI=1.443-4.222; p<0.001) were determinants of TB treatment success, with the type of health facility serving as the most dominant predictor of successful treatment outcomes.